2008
DOI: 10.1108/09590550810911674
|View full text |Cite
|
Sign up to set email alerts
|

The influence of grey consumers' service quality perception on satisfaction and store loyalty behavior

Abstract: PurposeThe purpose of this study is to identify grey consumers' perceived service quality at department stores and to examine the relationships between perceived service quality, their satisfaction and loyalty to those stores.Design/methodology/approachA structured questionnaire was developed to collect the data. Factor analysis was employed to identify dimensions of grey consumers' perceived service quality. Multiple regression analyses were conducted to examine the relationships between grey consumers' perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…Our approach of using positive WOM is consistent with the stream of research, which was exclusively interested in positive WOM comments (Gremler et al, 2001;Lu and Seock, 2008;Lymperopoulos and Chaniotakis, 2008). We are investigating the antecedents of positive WOM behaviors in a manner consistent with prior research (Maxham, 2001).…”
Section: Focal Constructsmentioning
confidence: 93%
“…Our approach of using positive WOM is consistent with the stream of research, which was exclusively interested in positive WOM comments (Gremler et al, 2001;Lu and Seock, 2008;Lymperopoulos and Chaniotakis, 2008). We are investigating the antecedents of positive WOM behaviors in a manner consistent with prior research (Maxham, 2001).…”
Section: Focal Constructsmentioning
confidence: 93%
“…Two key outcomes of CE that are of great interest to retail managers are satisfaction and loyalty (Burns and Neisner, 2006, Grewal et al, 2009, Lu and Seock, 2008, Martenson, 2007, Meyer and Schwager, 2007, Sivadas and Baker-Prewitt, 2000, Verhoef et al, 2009). …”
Section: Outcomes Of Customer Experiencementioning
confidence: 99%
“…In a New Zealand study of older consumers, Goodwin and Mcelwee (2001) showed that service quality and the availability of well-known brands were important characteristics for the oldest consumers. More recently, Lu and Seock (2008) identified three dimensions of service quality among American "grey" consumers: personal interaction, store image, and convenience. Personal interaction was the strongest predictor of older consumers' satisfaction and loyalty behaviour.…”
Section: Introductionmentioning
confidence: 99%